2016
DOI: 10.3389/fnagi.2016.00270
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Deterioration of Perineuronal Nets in the Primary Auditory Cortex of Mice

Abstract: Age-related changes in inhibitory neurotransmission in sensory cortex may underlie deficits in sensory function. Perineuronal nets (PNNs) are extracellular matrix components that ensheath some inhibitory neurons, particularly parvalbumin positive (PV+) interneurons. PNNs may protect PV+ cells from oxidative stress and help establish their rapid spiking properties. Although PNN expression has been well characterized during development, possible changes in aging sensory cortex have not been investigated. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 70 publications
3
41
0
Order By: Relevance
“…A loss of inhibition with age would be expected to result in changes in the functional responses, such as a broadening of FRAs. While we did observe a bandwidth difference between strains, our data showed higher frequency selectivity in C57 mice than CBA mice consistent with the higher baseline number of PV cells in these mice (Brewton et al, 2016). Additionally, any decrease in PV immunoreactivity in C57 mice might have not impaired the function of PV cells, or decreased PV cell function in C57 mice might have been compensated for by other classes of interneurons.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A loss of inhibition with age would be expected to result in changes in the functional responses, such as a broadening of FRAs. While we did observe a bandwidth difference between strains, our data showed higher frequency selectivity in C57 mice than CBA mice consistent with the higher baseline number of PV cells in these mice (Brewton et al, 2016). Additionally, any decrease in PV immunoreactivity in C57 mice might have not impaired the function of PV cells, or decreased PV cell function in C57 mice might have been compensated for by other classes of interneurons.…”
Section: Discussionsupporting
confidence: 75%
“…For example cells in the VNTB fire at lower rates in C57 mice than CBA mice at young ages (Sinclair et al, 2017) and deficits in the efferent feedback precede overt hearing deficits and could be observed by 8 weeks Zhu et al, 2007). By 6 months of age C57 mice also show a loss of parvalbumin immunoreactivity in A1 and AAF suggesting a loss or hypofunction of fast spiking (PV) inhibitory interneurons (Martin del Campo et al, 2012;Brewton et al, 2016). However, C57 mice show a higher number of PV cells than CBA mice at young ages indicating baseline strain differences in cortical circuits (Brewton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the auditory cortex, decreases in GAD65 and GAD67, two isoenzymes involved in GABA synthesis, are decreased in both aging Long-Evans and aging Fischer 344 rats, suggesting that chronological aging, rather than hearing loss, is responsible for this change [55]. The decrease in GABAergic neurons in the auditory cortex is seen in both parvalbumin-expressing and somatostatin-positive interneurons [65][66][67][68]. An examination of synaptic inhibition induced by thalamocortical transmission in a brain slice preparation revealed strong aging-related decreases in inhibition ( Figure 2) but found that the strongest predictor of the decrease in inhibition was an anatomical marker of chronological age (cortical thickness) and that the addition of hearing loss in a multiple regression model had no additional ability to predict the degree of GABAergic inhibition [69].…”
Section: Auditory Thalamus and Cortex Changesmentioning
confidence: 99%
“…Brain Sci. 2019, 9, x FOR PEER REVIEW 5 of 18 interneurons [65][66][67][68]. An examination of synaptic inhibition induced by thalamocortical transmission in a brain slice preparation revealed strong aging-related decreases in inhibition ( Figure 2) but found that the strongest predictor of the decrease in inhibition was an anatomical marker of chronological age (cortical thickness) and that the addition of hearing loss in a multiple regression model had no additional ability to predict the degree of GABAergic inhibition [69].…”
Section: Auditory Thalamus and Cortex Changesmentioning
confidence: 99%